Implementation of zero-based budgeting in corporate financial planning to improve operational cost efficiency - Santorry, Santorry (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study explores the implementation of Zero-Based Budgeting (ZBB) in corporate financial planning as a strategic approach to enhance operational cost efficiency. Utilizing a qualitative methodology, the research conducts a comprehensive literature review to analyze existing frameworks, case studies, and empirical evidence surrounding ZBB practices in various corporate settings. The findings indicate that ZBB, by requiring organizations to justify all expenses for each new period, fosters a culture of accountability and resource optimization. This budgeting method contrasts with traditional incremental budgeting, which often perpetuates inefficiencies and misallocations of resources. The literature reveals that companies adopting ZBB have reported significant improvements in cost management, operational flexibility, and strategic alignment of financial resources with organizational goals. Furthermore, the study identifies key challenges in the implementation of ZBB, including resistance to change, the need for robust data management systems, and the necessity for a shift in organizational mindset. The research concludes that while ZBB presents a viable solution for enhancing cost efficiency, its successful implementation requires a thorough understanding of organizational dynamics and a commitment to continuous improvement. This study contributes to the existing body of knowledge by providing insights into the practical implications of ZBB in corporate financial planning.